A Comparative Study Of The Indonesian Supreme Court's Decision and International Agreements on E-Commerce - Subadriyah Subadriyah; Arum Widiastuti (Jurnal Jurisprudence, 2025)
ABSTRACT Purpose of the Study: This research aims to analyze the relevance of Indonesia’s domestic regulations in governing e-commerce transactions, especially in the context of interstate taxation as well as evaluate how far these regulations are in line with international legal principles such as those regulated by United Nations Convention on the Use of Electronic Communications in International Contracts (UNECIC) and World Trade Organization (WTO). Methodology: This research utilized the normative juridical method with a legal comparison approach and a case approach on the Decision of the Supreme Court No. 1305/B/PK/PJK/2015. The data were qualitatively analyzed to identify regulatory gaps and suggest legal recommendations. Results: Research found that even though domestic regulations have regulated the e-commerce taxation aspect, there are still weaknesses in answering global challenges, such as server jurisdiction, the mechanism of resolving interstate disputes, as well as the protection of digital consumers. Supreme Court decisions have become a crucial foundation but have not fully referred to international standards. Applications of this Study: The results of this research can be used by policymakers, academicians, and legal practitioners as a basis for formulating more adaptive e-commerce regulations that are harmonious with international standards which support Indonesia’s digital economic ecosystem. Novelty/Originality of this Study: This research offers a constructive approach in bridging the gap between national regulations and international policies, as well as offering a scientific contribution through the integration of global principles into the domestic legal framework of e-commerce in Indonesia. Keywords: e-commerce, court decisions, international agreements, Indonesia.   ABSTRAK Tujuan Penelitian: Penelitian ini bertujuan untuk menganalisis relevansi peraturan perundang-undangan di Indonesia dalam mengatur transaksi perdagangan elektronik, khususnya dalam konteks perpajakan antarnegara, serta mengevaluasi sejauh mana peraturan perundang-undangan tersebut sejalan dengan prinsip-prinsip hukum internasional seperti yang diatur dalam Konvensi Perserikatan Bangsa-Bangsa tentang Penggunaan Komunikasi Elektronik dalam Kontrak Internasional (UNECIC) dan Organisasi Perdagangan Dunia (WTO). Metodologi: Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perbandingan hukum dan pendekatan kasus atas Putusan Mahkamah Agung No. 1305/B/PK/PJK/2015. Data dianalisis secara kualitatif untuk mengidentifikasi celah hukum dan memberikan rekomendasi hukum. Hasil: Penelitian menemukan bahwa meskipun peraturan perundang-undangan di Indonesia telah mengatur aspek perpajakan perdagangan elektronik, masih terdapat kelemahan dalam menjawab tantangan global, seperti yurisdiksi server, mekanisme penyelesaian sengketa antarnegara, serta perlindungan konsumen digital. Putusan Mahkamah Agung telah menjadi landasan krusial, namun belum sepenuhnya mengacu pada standar internasional. Aplikasi Studi Ini: Hasil penelitian ini dapat digunakan oleh para pembuat kebijakan, akademisi, dan praktisi hukum sebagai dasar untuk merumuskan regulasi e-commerce yang lebih adaptif dan selaras dengan standar internasional yang mendukung ekosistem ekonomi digital Indonesia. Kebaruan/Orisinalitas Studi Ini: Penelitian ini menawarkan pendekatan konstruktif dalam menjembatani kesenjangan antara regulasi nasional dan kebijakan internasional, serta memberikan kontribusi ilmiah melalui integrasi prinsip-prinsip global ke dalam kerangka hukum domestik e-commerce di Indonesia. Kata Kunci: e-commerce, putusan pengadilan, perjanjian internasional, Indonesia